"It's cancer screening after all". Barriers to cervical and colorectal cancer screening and attitudes to promotion of self-sampling kits upon attendance for breast cancer screening. (June 2023) - Kirkegaard, Pia; Larsen, Mette Bach; Andersen, Berit
Objectives: To explore barriers to cervical and colorectal cancer screening and attitudes to promotion of self-sampling kits upon attendance for breast cancer screening. Methods: Interview study with women who had not responded to one or more invitations to cervical or colorectal cancer screening. A semi-structured interview guide was used and interviews were audio recorded and transcribed verbatim. Concepts from Temporal Motivation Theory were used to structure and analyse the data. Results: Twenty-two women were interviewed. Screening was highly valued but the women perceived screening for cervical cancer and colorectal cancer as more troublesome to participate in, compared with participation in breast cancer screening. The lack of a pre-booked appointment or a suggested deadline attenuated the perceived value of cervical and colorectal cancer screening and this further increased procrastination. Promotion of self-sampling kits for cervical and colorectal cancer screening upon attendance for breast cancer screening was considered a feasible way to increase salience of both types of screening. Conclusion: A high number of micro steps and absence of a deadline in cervical and colorectal cancer screening diverted attention away from screening participation in cervical and colorectal cancer screening. The main facilitator could be reduction of micro actions, proposing a suggested deadline, and promotion of self-sampling kits when attending breast cancer screening to increase salience and a renewed attention to all three screening programmes.